Taking Care of Each Other: The Transformative Education for the Rebuilding of New Orleans after Hurricane Katrina - F. Fanizza; F. Spallone (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
In the framework of Disaster Studies, this article talks about the rebuilding of New Orleans after hurricane Katrina in 2005. It discusses aboutthe effects of transformative education with the aim to promote different approaches to facing disasters. Focusing the attention on the participatory planning processes, this article draws attention to the im- portance for a resilient community to develop a vision of its own future. For this reason, "taking care of each others" means the evaluation of the inner feelings of a community as crucial step both for the enlargement of citizenship awareness and for the social power improvement.